Business Cycle with Bank Intermediation in Oil Economies - Tabarraei, Hamid; Ghiaie, Hamed; Shahmoradi, Asghar (Washington, D.C. : International Monetary Fund, 2018)
The structural model in this paper proposes a micro-founded framework that incorporates an active banking sector with an oil-producing sector. The primary goal of adding a banking sector is to examine the role of an interbank market on shocks, introduce a national development fund and study its link to the banking sector and the government. The government and the national development fund directly play key roles in the propagation of the oil shock. In contrast, the banking sector and the labor market, through perfect substitution between the oil and non-oil sectors, have major indirect impacts in spreading shocks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet